2020
DOI: 10.15421/022021
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous and sequential influence of metabolite complexes of Lactobacillus rhamnosus and Saccharomyces boulardii and antibiotics against poly-resistant Gram-negative bacteria

Abstract: For the first time the poly-resistant strains of Gram-negative microorganisms were studied for the sensitivity to combined simultaneous and sequential influence of metabolic complexes of Lactobacillus rhamnosus GG and Saccharomyces boulardii, obtained by the author’s method without using the growth media, with antibiotics. The synergic activity of antibacterial preparations and metabolic complexes of L. rhamnosus GG and S. boulardii were studied using modified disk-diffusive method of Kirby-Bauer. During the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…It was difficult to isolate these pathogens during bacteriological studies (S. aureus was isolated predominantly) 22,23 . These results prove the potential for constructing based on metabolic complexes of lactobacilli and saccharomycetes of "accompaniments-preparations" to antibiotics for the treatment of wound infections 24,25,26 . Resistant to ciprofloxacin E. faecalis showed moderate resistance to the combined use of the antibiotic with the metabolite complex ML, despite a decrease in MIC by only half.…”
Section: Assessment Of the Sensitivity Of Multidrug-resistant Microormentioning
confidence: 54%
“…It was difficult to isolate these pathogens during bacteriological studies (S. aureus was isolated predominantly) 22,23 . These results prove the potential for constructing based on metabolic complexes of lactobacilli and saccharomycetes of "accompaniments-preparations" to antibiotics for the treatment of wound infections 24,25,26 . Resistant to ciprofloxacin E. faecalis showed moderate resistance to the combined use of the antibiotic with the metabolite complex ML, despite a decrease in MIC by only half.…”
Section: Assessment Of the Sensitivity Of Multidrug-resistant Microormentioning
confidence: 54%
“…Other studies have also evaluated antimicrobial combinations of the CFS of probiotic strains with antibiotic discs. For example, Isayenko et al [10] found an increase in the diameter of the zones of inhibition for A. baumannii when antibiotics were combined with the metabolite complexes of Lactobacillus rhamnosus (re-classified as Lacticaseibacillus rhamnosus) and Saccharomyces boulardii using the modified disk-diffusion method. Using the same method, in a recent study, Algburi et al [41] reported on the complementary activity of cefotaxime combined with the CFS of B. subtilis KATMIRA1933 and B. amyloliquefaciens B-1895 against methicillin-resistant Staphylococcus aureus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, effective approaches using antimicrobial combinations are urgently required as alternative and safe strategies to combat bacterial resistance to antibiotics. One of the suggested methods is using probiotics and their metabolites as antimicrobial substances in combination with conventional antibiotics to increase the sensitivity of pathogenic strains [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Чималу увагу приділяють проблемам антибіотикорезистентності та біоплівкоутворення бактерій, а також ролі метаболітів мікроорганізмів в цьому напряму [5][6][7][8]. Досі актуальні наукові дослідження у сфері інфекційних хвороб, спричинених стійкими до антибактеріальних препаратів збудниками, й участі похідних бактерій у зазначеному [9][10][11] Методи дослідження. Приготування інокулятів мікроорганізмів для дезінтеграції.…”
unclassified